2006
DOI: 10.1210/jc.2006-1546
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Leptin-Replacement Therapy and Possible Mechanisms of Leptin Actions in Patients with Generalized Lipodystrophy

Abstract: The present study demonstrates the efficacy and safety of the long-term leptin-replacement therapy and possible mechanisms of leptin actions in patients with generalized lipodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
152
1
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(176 citation statements)
references
References 39 publications
15
152
1
8
Order By: Relevance
“…1a), which can be seen in human obese individuals. In our clinical research on leptin-replacement therapy in patients with generalised lipodystrophy, the peak plasma leptin levels of the 400% dose under the protocol of once-daily injections was 34.5± 2.1 (mean±SE) ng/ml, and the therapy was well tolerated without any adverse effects for about 5 years [15]. In addition, higher leptin levels were obtained in the obese human clinical trial [33].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…1a), which can be seen in human obese individuals. In our clinical research on leptin-replacement therapy in patients with generalised lipodystrophy, the peak plasma leptin levels of the 400% dose under the protocol of once-daily injections was 34.5± 2.1 (mean±SE) ng/ml, and the therapy was well tolerated without any adverse effects for about 5 years [15]. In addition, higher leptin levels were obtained in the obese human clinical trial [33].…”
Section: Discussionmentioning
confidence: 81%
“…Recently, we and others confirmed that leptin treatment effectively reduces food intake and improves hyperglycaemia, hypertriacylglycerolaemia and fatty liver in patients with lipoatrophic diabetes [13][14][15][16]. In addition, we demonstrated that leptin is useful as a glucose-lowering agent in a mouse model of insulin-deficient diabetes induced by high-dose streptozotocin (STZ) [11].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…This is corroborated by recent clinical and animal investigations that excess as well as complete absence of fat in the body are concomitant with hyperinsulinemia, insulin insensitivity and diabetes. 7,[22][23][24][25][26][27][28] The discovery of insulin in 1922 and the subsequent development of insulin analogs have been the life-saving treatments of hyperglycemia and in delaying or preventing the array of chronic complications of diabetes mellitus. 2,13,[29][30][31] Diabetes, therefore, has traditionally been viewed as an affliction of either lack of or incomplete use of insulin and, consequently, conventional research has focused entirely on improving ways to deliver insulin for precision in attaining glycemic control to simulate the physiological range of blood glucose, necessary to combat the comorbidity cluster of this chronic malady.…”
Section: Introductionmentioning
confidence: 99%